Studi Etnofarmasi Etnis Using Banyuwangi Indonesia - Nailis Syifa; Apris Dwi Sihdianto; Adityo Herjuno; Alvan Febrian Salash (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2011)
Cultural studies about treatment methods and herbal plants in an ethnic important to understand in order to know the different methods of treatment and medicinal plants used from each ethnicity. In addition, this study is also useful to know the drugs from natural ingredients that have not been identified. In this study, as the object of research is ethnic Using, Kemiren village, District Glagah Banyuwangi. The method used in this study include interviews with local community and the people who play a role in traditional medicine in these ethnic. The results obtained information on 62 commonly used medicinal plants for traditional medicine. From 62 plants were then performed classification based on the bioactivity.